2020
DOI: 10.1111/jcmm.15411
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐derived exosomal miR‐3473b promotes lung tumour cell intrapulmonary colonization by activating the nuclear factor‐κB of local fibroblasts

Abstract: Tumour‐derived exosomes have been shown to induce pre‐metastatic niche formation, favoring metastatic colonization of tumour cells, but the underlying molecular mechanism is still not fully understood. In this study, we showed that exosomes derived from the LLC cells could indeed significantly enhance their intrapulmonary colonization. Circulating LLC‐derived exosomes were mainly engulfed by lung fibroblasts and led to the NF‐κB signalling activation. Further studies indicated that the exosomal miR‐3473b was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…2 A). However, our previous study showed that LLC-derived exosomes promoted LLC colonization in the lung 25 . So, LLC-Exo are not an appropriate carrier to deliver miR-29a-3p.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…2 A). However, our previous study showed that LLC-derived exosomes promoted LLC colonization in the lung 25 . So, LLC-Exo are not an appropriate carrier to deliver miR-29a-3p.…”
Section: Resultsmentioning
confidence: 88%
“…Tumor-derived exosomes participate in tumor progression and metastasis by communicating with the tumor microenvironment are vital to establishing the pre-metastatic niche (PMN) 18 , 32 , 33 , 34 . Our previous study identified that lung tumor cell-derived exosomes facilitate lung tumor cell colonization in the lung by activating NF- κ B signaling of lung fibroblasts 25 . Similarly, the uptake of breast cancer-derived exosomes by lung fibroblasts promoted their activation and fibronectin secretion, thus contributing to PMN formation and lung metastasis 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the regulatory role of miRNAs in a variety of diseases has been confirmed. Mir‐3473b is a miRNA involved in the inflammatory response in a variety of diseases (Du et al., 2020; Wang et al., 2018; Wu et al., 2014). The results of the in vivo and in vitro experiments of the present study are the first to confirm the role of mir‐3473b in PD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, through the carried molecules, particularly integrins, tumor exosomes can specifically target different organs or tissues and prepare the pre-metastatic niche [102]. Lewis lung carcinoma cell line produces exosomes containing miR-3473b, which once captured by lung fibroblasts cause NF-kB activation and inflammatory cytokines production, enhancing their intrapulmonary colonization [103]. Lung cancer commonly metastasizes to the brain and bone.…”
Section: Exosomes Promote Lung Cancer Growth and Metastasismentioning
confidence: 99%